2018
DOI: 10.1039/c7en00985b
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of titanium dioxide nanoparticles with soil components and plants: current knowledge and future research needs – a critical review

Abstract: Titanium dioxide nanoparticles (nano-TiO2), one of the most produced engineered nanoparticles (ENPs), are used in pigments, photocatalysis, food additives, and personal care products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(99 citation statements)
references
References 153 publications
3
96
0
Order By: Relevance
“…Among those three major polymorphs, anatase is extensively applied in commercial products due to its higher activity comparing to other forms, although rutile is the more stable form (Chen and Mao, 2007;Zhang et al, 2015). Additionally, there are no commercial TiO 2 NPs products in the brookite phase (Tan et al, 2018). Titanium is a common metal in soil that occurs in naturally occurring nano-sized particles, such as clays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those three major polymorphs, anatase is extensively applied in commercial products due to its higher activity comparing to other forms, although rutile is the more stable form (Chen and Mao, 2007;Zhang et al, 2015). Additionally, there are no commercial TiO 2 NPs products in the brookite phase (Tan et al, 2018). Titanium is a common metal in soil that occurs in naturally occurring nano-sized particles, such as clays.…”
Section: Introductionmentioning
confidence: 99%
“…The wide applications of TiO 2 NPs have raised serious concerns regarding their potential threat to the environment, as during their whole life cycle, TiO 2 NPs may be released into the air, soil, and/or water, affecting all components of the environment, including plants, which are directly exposed to these emerging contaminants (Oliver et al, 2015;Tan et al, 2018). It has been reported that the emission of TiO 2 NPs represents more than one-fourth of the estimated mass flow of engineered nanoparticles (ENPs) in a worldwide range (Keller and Lazareva, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are a limited number of papers concerning titania toxicity in higher plants [ 195 , 196 ]. Tan et al [ 197 ] have summarized the interaction between nano-TiO 2 and plants, including detection techniques, and possible effects of titania properties, such as the particle size, crystal phase, and surface coatings, as shown in Figure 10 . Studies on the model plant Aribidopsis thaliana , crops and horticultural plants, such as Allium cepa, Avena sativa, Cucumis sativus, Nicotiana tabacum, Spinacia oleracea, Zea mays, Oryza sativa, Brassica campestris ssp.…”
Section: Toxicity Of Titanium(iv) Oxidementioning
confidence: 99%
“…Blue box summarized the major findings in the study of each growth stage (orange box). Adapted from reference [ 197 ] with permission from Royal Society of Chemistry, 2018.…”
Section: Figurementioning
confidence: 99%
“…The functionalization and coating of nanomaterials alter the adsorption and accumulation ability within the plants. Some of the nanomaterials might accumulate at Casparian strip, whereas another translocate with symplastic routes towards shoot and root [84].…”
Section: Interaction Of Polymeric Nanocomposite With Plantsmentioning
confidence: 99%